An investigation into the growing importance of user-generated content within the realm of contemporary digital marketing endeavors - Anupkumar Dhore; Apurva Khobragade; Toshik Arun Mowade (Journal of Management and Science, 2023)
The performance of athletes is greatly influenced by their diet, as it supplies the essential nutrients and energy needed to sustain their bodies. Meeting the specific nutritional needs of sportspeople is crucial for maintaining their overall physical and mental well-being, as well as supporting their training and competitive objectives. This review paper aims to examine the significance of diet in sports, with a particular focus on the role played by macronutrients, micronutrients, hydration, meal timing, and other relevant factors. By delving into the topic, this research paper investigates the value of a well-balanced diet in sports and its direct impact on athletic performance. Furthermore, it sheds light on the specific types of foods and nutrients that athletes should consume in order to optimize their performance.